Pretreatment strategies for delignification of sugarcane bagasse: a review - Susan Grace Karp; Adenise Lorenci Woiciechowski; Vanete Thomaz Soccol; Carlos Ricardo Soccol (Brazilian Archives of Biology and Technology, 2013)
The valorization of agro-residues by biological routes is a key technology that contributes to the development of sustainable processes and the generation of value-added products. Sugarcane bagasse is an agro-residue generated by the sugar and alcohol industry in Brazil (186 million tons per year), composed essentially of cellulose (32-44%), hemicellulose (27-32%) and lignin (19-24%). The conversion of sugarcane bagasse into fermentable sugars requires essentially two steps: pretreatment and hydrolysis. The aim of the pretreatment is to separate the lignin and break the structure of lignocellulose, and it is one of the most critical steps in the process of converting biomass to fermentable sugars. The aim of this review is to describe different pretreatment strategies to promote the delignification of the sugarcane bagasse by thermo-chemical and biological processes.